Project benefits management - a survey - Baccarini, David; Bennington, P. (Project Management Global, 2003)
Information technology (IT) projects are implemented to provide benefits to the organisation. This paper reports some of the research findings into the process of benefits management by project managers in IT projects in Perth, Western Australia. The information was gathered from in-depth structured interviews with IT project managers from twenty-five organisations.The key conclusions are: Project managers agree for the need to improve benefits management processes but paradoxically there are many examples of poor benefits management Project managers overstate the benefits to gain project approval, so it is not surprising that senior management has doubts that IT delivers real business benefits. IT projects managers have a strong leaning towards efficiency benefits, indicating a lack of awareness of IT projects' role in achieving effectiveness benefits